Ferric Carboxymaltose in the Treatment of Anemia in Patients with Locally Advanced Colon Cancer - D. O. Kornev; A. N. Moskalenko; E. S. Kuzmina; V. K. Lyadov (Креативная хирургия и онкология)
Introduction. The incidence of anemia in colorectal cancer patients reaches 30–67% depending on the stage and location of the tumor; the presence of anemia adversely affects the short-term and long-term results of radical treatment. One possible way of anemia correction is to parenterally administer iron preparations, specifically ferric carboxymaltose (III), prior to cancer treatment.Materials and methods. The efficacy of anemia correction through intravenous administration of ferric carboxymaltose (III) in prehospital care was retrospectively evaluated in Stage II–III colon cancer patients who were treated at the Oncology Center No. 1 of the S.S. Yudin City Clinical Hospital (Moscow) from June 2022 to February 2023. The study group included 103 patients who underwent primary tumor removal (Group 1) and 61 patients who received chemotherapy (Group 2). The mean hemoglobin level prior to correction with parenterally administered iron preparations amounted to 92.12 ± 10.75 g/L in both groups. Mild anemia was observed in 58% of patients; moderate, in 39% of patients; severe, in 3% of patients. The average amount of ferric carboxymaltose (III) received by each patient in both groups was 982.58 ± 102.93 mg. The hemoglobin and iron levels were, on average, monitored on day 14 in both groups. Results. In the entire sample, the hemoglobin and iron levels, on average, increased to 113.7 ± 11.0 g/L (p < 0.0001) and 20.3 ± 9.1 µmol/L (p < 0.0001), respectively. On average, the hemoglobin level increased by 21 ± 11.5 g/L (p = 0.01086), and the iron level rose by 15.7 ± 9.4 µmol/L (p = 0.038). Following correction, no severe anemia was observed; moderate and mild anemia was noted in 2% and 80% of patients, respectively; 18% of patients had no anemia (p < 0.0001).Discussion. The correction of anemia through intravenous administration of ferric carboxymaltose (III) to colorectal cancer patients at the outpatient stage was found to be safe and efficacious.Conclusion. The administration of ferric carboxymaltose (III) to colorectal cancer patients with iron deficiency anemia 14 days prior to the cancer treatment enabled a statistically significant increase in hemoglobin levels and a drastic reduction in the number of patients with moderate and severe anemia.